On measuring diversity and similarity from abundance and incidence ecological data the case of avifaunal communities in Mindanao - Mata, May Anne (2007)
Biodiversity of different communities can be analyzed using diversity and similarity measures. However, these measures are dependent to the ecological data used. For instance, traditional similarity measures (Jaccard and Sorensen) only utilize incidence (presence ?absence) data while diversity measures (Shannon and Gini-Simpson) only utilize abundance data. On the other hand, Rao diversity and dissimilarity coefficients have been found to handle both ecological data yet, take into account the differences among species in the communities unlike the traditional measures. Since the study primarily aimed at determining how ecological data affect these measures, traditional were extended to handle both ecological data while the general index of Rao coefficients were particularized to handle abundance and incidence data. These developed methods were tested using the ecological data from five avian communities in Mindanao (Agusan Marsh, Binoongan Forest Reserve, Mt. Mahuson, Mt. Sinaka, and Mt. Talomo). The interpretation and analyses regarding the relationships between communities and species according to similarity were supported by ordination methods like Double Principal Coordinate Analysis (DPCoA) and Principal Coordinate Analysis (PCoA) Based on the findings, incidence data maximized the diversity index of communities. Moreover, modified traditional measures yielded essentially similar interpretation whether abundance and incidence data was used. Rao coefficients, nevertheless, differed most with other measures due to the consideration of species differences as well as identification of conservation priority. Generally, the methods developed in the study introduced new combination of approaches for the ecologists in analyzing the communities using the available ecological data